Hindrance stressors, ego depletion and knowledge sharing - Fei Kang; Ying Zhang; Han Zhang (Organization Management Journal (OMJ), 2022)
Purpose - This study aims to use the ego depletion theory to examine the impact of hindrance stressors on knowledge sharing behaviors by investigating the mediating role of ego depletion and the moderating role of self-enhancing humor. Design/methodology/approach - Data were obtained from a two-wave sample of 226 dyads, including employees in the manufacturing industry and their direct supervisors. The hypotheses were tested by hierarchical regression analyzes and Hayes' PROCESS macro. Findings - The results demonstrated that employees' self-enhancing humor style could alleviate the impact of hindrance stressors on employees' ego depletion state and buffer the negative indirect effect of hindrance stressors on employees' knowledge-sharing behaviors. Research limitations/implications - Although the authors collected mediator and dependent variables from different sources, this study used a cross-sectional research design, making it difficult to draw causal conclusions. Besides, hindrance stressors, ego depletion and self-enhancing humor style were all reported by employees. Originality/value - Through the study, the authors highlight the important role of the self-control view in explaining proactive behavior in the workplace and a great awareness of the unforeseeable consequences of ego depletion for employees.
Keywords: 650; Knowledge sharing; Self-enhancing humor; Ego depletion; Moderated mediation model; MHindrance stressors